1971
DOI: 10.1021/jo00806a037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of .beta.-substituted pyrroles via 1-(pyrrol-2-ylmethylene)pyrrolidinium salts

Abstract: rapidly to resemble those characteristic of the disulfide, indicate that 2-nitro-5-mercaptobenzoic acid is exceedingly sensitive to aerial oxidation.Since it was not practical to prepare a sample of pure 2-nitro-5-mercaptobenzoic acid, its molar absorptivity was calculated from the absorbance of a solution of the disulfide in aqueous phosphate buffer to which sufficient aqueous solution of sodium thioglycolate had been added to produce maximal absorbance (Table II). A solution of exactly the same Table II Abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…(98) It has been reported that the bromination of 2-acetylpyrrole in acetic acid produces only the 4-bromo product, (99) and, similarly, 4-bromo-2-nitropyrrole is the major product (>90%) of the bromination of 2-nitropyrrole in CC1 4 , with virtually no dibromination products being formed. (98) It has been reported that the bromination of 2-acetylpyrrole in acetic acid produces only the 4-bromo product, (99) and, similarly, 4-bromo-2-nitropyrrole is the major product (>90%) of the bromination of 2-nitropyrrole in CC1 4 , with virtually no dibromination products being formed.…”
Section: Brominationmentioning
confidence: 96%
“…(98) It has been reported that the bromination of 2-acetylpyrrole in acetic acid produces only the 4-bromo product, (99) and, similarly, 4-bromo-2-nitropyrrole is the major product (>90%) of the bromination of 2-nitropyrrole in CC1 4 , with virtually no dibromination products being formed. (98) It has been reported that the bromination of 2-acetylpyrrole in acetic acid produces only the 4-bromo product, (99) and, similarly, 4-bromo-2-nitropyrrole is the major product (>90%) of the bromination of 2-nitropyrrole in CC1 4 , with virtually no dibromination products being formed.…”
Section: Brominationmentioning
confidence: 96%
“…The synthesis of both biaryl carbaldehydes (1 and 2) was achieved using Suzuki-Miyaura coupling conditions [14] that used tetrakis(triphenylphosphine)palladium (0) [(Ph 3 P) 4 Pd(0)], 1,2-dimethoxyethane (DME)/H 2 O, sodium carbonate (Na 2 CO 3 ), and the previously synthesised 4-bromo-1H-pyrrole-2carbaldehyde. [15,16] The commercially available 2-thiophene boronic acid and the readily synthesised 1-(tert-butoxycarbonyl)-1H-pyrrol-2-ylboronic acid [17] were the boronic acid derivatives used for the synthesis of compounds 1 and 2, respectively (Scheme 1). Chromatographic purification of the individual reaction mixtures afforded pure 4-(2'-thienyl)-1H-pyrrole-2-carbaldehyde (1) and tert-butyl-2-(5'-formyl-1H-pyrrol-3'-yl)-1H-pyrrole-1-carboxylate (2) in yields of 78% and 23%, respectively.…”
Section: Synthesis Of the Biaryl Carbaldehydesmentioning
confidence: 99%
“…Silica chromatography on the reaction mixture yielded the dialkylated amine, N,N-bis{ [4-(2- (9). The presence of the dialkylated amine (15) suggested that the reduction of 14 was very slow and as a result, the small amount of produced monoalkylated amine (9) had sufficient time to either react with the aldehyde (1), produced by hydrolysis of the imine (14), or the imine (14) itself, to produce the dialkylated amine (15). The problem of dialkylation when performing reductive aminations using certain aldehydes and 1 amines has been reported in the literature, and this problem is usually rectified by adopting a stepwise procedure involving imine formation followed by the reduction using sodium borohydride (NaBH 4 ) in an alcoholic solvent.…”
Section: Synthesis Of the Amine Combinatorial Librarymentioning
confidence: 99%
“…1H-Pyrrole-2-carbaldehyde 2a was prepared from freshly distilled 1H-pyrrole by VilsmeierHaack formylation. 9 Freshly distilled 1H-pyrrole was also used to prepare 1H-pyrrole-2,4-dicarbaldehyde 2b, by reacting with oxalyl chloride in DMF and then formylating the pyrrole 2c was synthesised by the method of Sonnet 11 that is, bromination of the ternary iminium salt, obtained from 1H-pyrrole-2-carbaldehyde 2a and pyrrolidinium perchlorate in benzene, followed by mild hydrolysis. The synthesis of enamides 2d and 7 was accomplished in two steps.…”
Section: Introductionmentioning
confidence: 99%